Design and development of traffic light fault detection system - Che Soh, Azura (2001)
Traffic light is normally installed at junctions to ensure smooth running of traffic. It is common to see a little signboard that displays telephone number to contact in case of malfunction. This solely depends upon the willingness of the road users to inform the authority. It may be malfunction for a day or more. This in turn will create problem to the users. Therefore, an automatic fault detection system that will send a message to the authorities would be required. In order to do that, a survey has been conducted to evaluate the behaviour of road users when approaching a junction. Based on that, different failures were grouped into three categories i.e. Highly Critical, Critical and Non Critical. A system to detect the condition of the lights based on the categories has been developed using photodarlington and combinational logic. The system has been simulated, implemented and tested successfully. Output of the system is fed to a microcontroller based system that will send out messages to control room when failures occurs which will then be displayed together with the category of the failure. The system is now ready to be tested on the real traffic lights.